Genetic analysis for seed yield and yield‐related traits in tepary bean (Phaseolus acutifolius A. Gray) under drought‐stress and non‐stress conditions - Mwale, Saul Eric; Shimelis, Hussein; Nkhata, Wilson; Sefasi, Abel; Fandika, Isaac; Mashilo, Jacob (Wiley, 2024)
Tepary bean ( Phaseolus acutifolius A. Gray) is an under‐utilized genetic resource with significant potential for food security and stress tolerance breeding. Expanding its cultivation in southern Africa requires high‐yielding, locally adapted and drought‐tolerant varieties. This study determined the combining ability and genetic components for seed yield and related traits in tepary bean genotypes under non‐stress (NS) and drought‐stress (DS) conditions. Seven parents were selected through rigorous phenotyping and crossed using a half‐diallel design. The 7 parents and 21 F 2 progenies were evaluated in 2021/2022 season at Kasinthula and Bunda sites in Malawi under NS and DS conditions using a 4 × 7 lattice design with three replications. The specific combining ability (SCA) × location interaction effect was significant ( p < 0.05) for DTF, NPP, and SY, suggesting that the genetic effects of crosses were influenced by the test locations. General combining ability (GCA) and SCA mean squares were significant for the number of seeds per pod (NSP) and SY under DS conditions, indicating both additive and non‐additive gene effects. Baker's ratio (BR) > 0.50 for NPP and NSP under DS conditions suggested a preponderance of additive gene effects. G40145, G40148 and G40150 parental lines were good combiners for NPP and SY. The F 2 families from crosses such as Zimbabwe landrace/G40138, Zimbabwe landrace/G40150, G40059/G40145, G40059/G40148, G40138/G40150 and G40145/G40150 were identified as best specific combiners, with enhanced SY of 1.67 t/ha under DS conditions. The study recommends advancing high‐performing early‐generation families for selection across representative environments to facilitate variety release and commercialization.